2020
DOI: 10.1021/acs.jafc.0c01421
|View full text |Cite
|
Sign up to set email alerts
|

Digestion of Intact Gluten Proteins by Bifidobacterium Species: Reduction of Cytotoxicity and Proinflammatory Responses

Abstract: Celiac disease (CD) is a chronic illness characterized by an inflammatory process triggered by gluten protein intake. Recent evidence has suggested that the lower relative abundance of bifidobacteria in the intestinal lumen may be associated with CD. Herein, we assessed the effect of the Bif idobacterium species Bifidobacterium bifidum, Bifidobacterium longum, Bembidion breve, Bifidobacterium animalis alone, and also a Bif idobacterium consortium on the digestion of intact gluten proteins (gliadins and gluteni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 46 publications
(80 reference statements)
1
8
0
Order By: Relevance
“…Our results are in the same line as others that assure that differences in the microbiota across different body sites are enough for grouping samples [72]. Permutational multivariate analysis of variance (PERMANOVA) for each variable by ADONIS function revealed that Study Accession, in the case of the duodenum, saliva, and stool, was a factor influencing the grouping of samples.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Our results are in the same line as others that assure that differences in the microbiota across different body sites are enough for grouping samples [72]. Permutational multivariate analysis of variance (PERMANOVA) for each variable by ADONIS function revealed that Study Accession, in the case of the duodenum, saliva, and stool, was a factor influencing the grouping of samples.…”
Section: Resultssupporting
confidence: 90%
“…Also, we found an enrichment in Akkermansia , a bacteria associated with anti- inflammatory properties and metabolic health [71]. Despite the beneficial changes observed, stool microbiota of patients undergoing GFD presented a decrease in Lactobacillus, and Bifidobacterium , SCFA producers bacteria, which also digests intact gluten proteins reducing cytotoxicity and inflammatory responses [15, 72], and the presence of bacteria associated to CeD such as Bacteroides , and Pseudomonas both genus with species containing metalloproteases able to partially digest gluten, increasing the immunogenic effect of gliadins inducing more severe inflammation [73, 74].…”
Section: Resultsmentioning
confidence: 99%
“…The administration of the same B. longum strain has also been shown to decrease jejunal TNF-a levels in an in vivo model of gliadin-induced enteropathy (23). Recently, the effect of Bifidobacterium species, namely B. bifidum, B. animalis, B. breve, and B. longum, on the hydrolysis of unmetabolized gluten proteins as well as on the related toxic effect and immune responses elicited by the resulting peptides, has been investigated (20). The different individual species and a mixture of the four Bifidobacterium species resulted in diverse peptide patterns, deriving from the principal wheat protein classes, namely gliadins and glutenins, and presenting from 15 to 40 long amino-acid residues.…”
Section: Probiotics and Wheat Deglutinationmentioning
confidence: 99%
“…Therapy with probiotics containing bacteria that can degrade gluten could be a possible new strategy for the complementary treatment of CeD patients [ 126 ]. Bifidobacterium species showed significant digestion of gluten protein and reduced cytotoxicity and pro-inflammatory responses [ 127 ]. A probiotic preparation (two strains of Lactobacilli and three strains of Bifidobacteria ) hydrolyzes the gliadin peptides and protects intestinal cells from the toxic pro-inflammatory peptides [ 128 ].…”
Section: Dietary Interventions For Complementing the Gfd And Beyondmentioning
confidence: 99%